Fully quantal close-coupling approach to antiproton-hydrogen collisions - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Bray, Igor; Stelbovics, Andris (2012)
A fully quantal close-coupling integral-equation approach to antiproton-hydrogen collisions has been developed. Integral and fully differential cross sections have been calculated.